Pemahaman Nature of Science (Hakekat IPA) Bagi Guru IPA: Solusi Membelajarkan IPA Multidimensi - Muh. Zaini Hasanul Muttaqin; Muhammad Sarjan; Joni Rokhmat; Agus Muliadi; Asrorul Azizi; Bachtiar Ardiansyah; Hamidi Hamidi; Iswari Pauzi; Muhammad Yamin; Mulia Rasyidi; Rindu Rahmatiah; Sudirman Sudirman; Yusran Khery (Jurnal Ilmiah Wahana Pendidikan, 2022)
This article aims to examine the importance of understanding the nature of science for science teachers as a solution in teaching multidimensional science. Science is a knowledge (scientific product), a series of investigation processes (scientific process), and scientific attitude which is reflected in the nature of Science (Nature of Science). NOS describes the real science, how it works, and its interaction with society in the perspectives of philosophy, history, sociology, and psychology of science. Understanding NOS is an important aspect of scientific literacy. The results of research in recent times show that teachers and students do not understand the concept of NOS optimally. This study uses literature analysis. The results show that NOS is divided into three main aspects, namely the nature of scientific knowledge, the nature of scientific investigation and the nature of scientific endeavor. understanding the concept of NOS must be an important part to be instilled in science teachers. Learning science is not just knowing natural objects, but science has a wider study dimension than that, which needs to be studied from the ontological, epistemological and axiological side. Teachers must master how to teach science, how the impact or influence of science learning and what influences science learning. Thus, understanding the NOS concept of science teachers will have an impact on students' mastery of understanding the NOS concept.